Awareness and Practice of Contraception among Women Coming to Civil Hospital Karachi - Rabeeya Razaque, Aneela Habib, Sana Shameer, Gulfishan Tariq, Shakira Perveen, Sarah Kazi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the awareness and practices of contraception among women coming to Civil Hospital Karachi. Methods: A total of 196 women of reproductive age (15 to 49 years) attending the labor room, emergency room and outpatient department of Civil Hospital Karachi from 25th of November 2020 to 26th of May 2021 were included. We included Previously delivered as well as undelivered married females who were able to communicate in local language. Data was collected regarding awareness medium and husband’s willingness or role regarding contraception. Results: The average age of the patients was 25.91±4.48 years. Median number of children was 1 [range=1-5] and average pregnancy interval was 11.13±3.49 months. Most of the female (81.12%) were Muslims. There were 112 (57.14%) female who had previous experience of contraception. Awareness and practices of contraception among women was 87 (44%) and 107 (55%) respectively. Conclusion: According to the findings of our Study, 44% of women are aware of and use contraception, whereas 55% of women use contraception. A large part of this is due to a lack of knowledge about its benefits, a lack of resources, and insufficient information about the various ways. Keywords: Contraception, Family planning, contraception practices.